PENGARUH SIKAP PROFESIONAL, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU SEKOLAH MENENGAH ATAS NEGERI KOTA SUNGAI PENUH - eliya sartika; bustari muchtar (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
The purpose of this research is to revealy influence the professional attitudes,  work motivation and work discipline on the teachers performance in at the Senior High Schools Sungai Penuh City. The research population is the teachers who civil servants and  the sample taken are 141 teachers as respondents with proporsional stratified random sampling. The technical data collecting by questioner and document. The approach which has been used in this reseach is descriptive and data processing by using SEM technique and  Lisrel 8.30 program. The result of this research shows that: 1)The professional attitudes significantly influence on the work discipline of teachers 2)The professional attitudes indirectly significantly influence on the work motivation, 3)The professional attitudes significantly  influence on the teachers performance, 4) Work motivation significantly influence on the teachers performance , 5)Work discipline significantly influence on the work motivation of teachers, 6)Work discipline indirectly significantly influence  on the teachers performance. Therefore,it suggested that to increase teachers performance is necessary to increase both professional attitudes through work discipline and work motivation. Keywords: professional attitudes, work motivation, work discipline, and the teachers performance